2019
DOI: 10.5897/err2019.3784
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between self-sabotage and organizational climate of schools

Abstract: This study aimed to determine the relationship between self-sabotage behaviours of school administrators and teachers and their perceptions of organizational climate in schools. In the present study, "correlational screening model" which is a quantitative research method was used. A sample consisting of 1204 teachers and 166 administrators working in 74 Turkish schools was selected through stratified cluster sampling method to carry out this study. In order to measure self-sabotage levels of teachers and admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…Therefore, educational administrators must ensure that their faculty members are content and committed to the school. Studies and research have shown that contented workers are more loyal to their companies (Hoyt, 2012;Gokce, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, educational administrators must ensure that their faculty members are content and committed to the school. Studies and research have shown that contented workers are more loyal to their companies (Hoyt, 2012;Gokce, 2013).…”
Section: Introductionmentioning
confidence: 99%